Psychology of Al-Fatiha Psychological Foundations in Spiritual Pedagogy - Najah Hanim Binti Mohd Hamidi; Hawa Khoirunnisa; Naan Naan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Basically, this discussion emphasizes the core purpose of spiritual pedagogy and themedium of the psychic dimension based on surah al-Fatiha. As we know, Psychology is the study ofscience that discusses various information about human life and symptoms related to aspects of thehuman in person at certain stages of development to recognize and respond to themselves and otherhumans in accordance with their development. As a Muslim, this obligation to learn to recognizeoneself is required to be based on the Qur'an and al-Hadith, while the Qur'an itself has providedvarious discussions about the